Komitmen Perkawinan Pasangan yang Berlatar Belakang Anak Sulung: Penelitian - Agus Wahyudi; Fatma Nofriza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Maintaining marital commitment for married couples requires very strong fighting power. Especially for married couples who come from the status of the firstborn in the family. Firstborns have a tough personality and prefer to keep their problems to themselves, so many of them grow up with a tough nature and do not like to trouble others in their own lives. With a partner who happens to have a background as the firstborn, of course, many face challenges in adjustment. This study aims to investigate the marital commitment of two firstborn couples. The household has been lived for ten years. The results show that the first couple has very prominent aspects of personal and moral commitment, while the second couple has prominent moral and structural aspects in their household